Periodisasi Sejarah Sastra Masa Andalusia: (Kajian Historis) - Nisa’, Ida Chairun; Budi, Rahmat Dinni Haerul (Rihlah: Jurnal Sejarah dan Kebudayaan, 2024)
The periodization of Arabic literature in Andalusia as shown by historians differs from one another. This is interesting to research, especially examining the differences in periodization. This research aims to find a reliable chronology of the periodization of the history of Arabic literature in Andalusia. To find the correct chronology of the periodization of Arabic literary history, researchers use historical methods. Researchers found the following periodization: chronologically, the historical periods of Arabic literature in Andalusia are divided into six. First, 711-755 AD, no literary manuscripts have been found. Second, 755-912 AD, literary texts were found under Ad-Dakhil’s reign but were still oriented towards Masyriq literature. Third, 912-1013 AD, namely the period when the group of kings called "Mulukut Tawaif" was formed and literary critics began to appear. Fourth, 1013-1086 AD, literature at this time was still oriented towards Masyriq literature but the difference lay in the ability of Andalusian writers to use more real and imaginative wording. Fifth, 1086-1248 AD, during this time poets and philosophers emerged, among the famous ones being Ibnu Thufail and Ibnu Rushd. Sixth, 1248-1492 AD, during this period lament literature began to be introduced and continued to develop rapidly.